Active booming noise control system for automobiles. (4th August 2014) - Kinoshita, A.; Tabata, T.; Doi, K.; Nakaji, Y.
A basic study on active noise control (ANC) was carried out with the aim of reducing booming noise. The interior sound field was analysed in terms of both time and spatial variability. The results showed that a multi–channel adaptive algorithm is necessary for global control. In addition, acoustic system optimization was studied to maximize control performance. As a result, a prototype ANC system was built and tests conducted in an actual vehicle revealed that it reduced booming noise by more than 10 dB.